Electron and Photon Energy Spectra Outside of 6 MV X-ray Small Radiotherapy Field Edges Produced by a Varian iX Linac - Xicohténcatl-Hernández, Nahum; Moreno-Ramirez, Adriana; Massillon-JL, Guerda (Frontiers in Physics, 2021)
Due to the increase in the survival probability for patients treated with modern radiotherapy techniques to live enough for experimenting late radiation-effect, low-dose outside the treatment volume becomes a concern. However, besides absorbed-dose, the beam quality outside the field-edge should be taken into account. This work aimed at investigating the photon and electron fluence spectra outside the field-edges for several small radiotherapy-fields for determining the quality of the beams in order to better evaluate secondary effect after modern radiotherapy treatments. Phase-space files of a 6MV X-ray beam produced by a Varian iX linac for eight small fields of 0.7x0.7 cm2, 0.9x0.9 cm2, 1.8x1.8 cm2, 2.2x2.2 cm2, 2.7x2.7 cm2, 3.1x3.1 cm2, 3.6x3.6 cm2, 4.5x4.5 cm2 and the reference 10 x10 cm2 field at SSD=100cm were generated using the BEAMnrc code. The photon and electron fluences in each field were calculated at 0.15 cm, 1.35 cm and 9.85 cm water-depth and several off-axis distances using FLURZnrc. The number of low-energy electrons between 1keV and 10keV at 2 cm outside the field-edge increases by 60% compared to the central-axis. Due to the relatively high linear energy transfer (LET) of these electrons, the results of this work should help to better evaluate possible late effect of secondary radiation on heathy organs close to the tumour volume after radiotherapy treatment. We also observed high-energy electrons outside the field-edge that are attributed to leakage of the primary electron beam from the head of the linac. From a standpoint of radiological protection, these electrons should be taken into account when evaluate the dose delivered to the patient skin